A Dog Day; or, The Angel in the House - Emanuel, Walter, 1869-1915; Aldin, Cecil, 1870-1935 (Salt Lake City, UT : Project Gutenberg, 2016)
"A Dog Day; or, The Angel in the House" by Walter Emanuel is a humorous narrative written in the early 20th century. This whimsical book can be classified as a light-hearted fiction or a novella, told from the perspective of a dog. The narrative explores the everyday adventures and thoughts of the canine protagonist, offering a playful glimpse into the domestic life and interactions with human characters. The story unfolds over a single day in the life of a delightful dog living with the Brown family. Through the dog's eyes, readers experience a variety of amusing episodes, including a heroic encounter with a burglar, adventures involving tumultuous relationships with cats and family members, and culinary mischief as he sneaks food. The tone is lively and expresses the dog's carefree outlook on life filled with joyful antics, moments of affection, and the occasional reprimand. With whimsical charm and humor, the book captures both the innocence and playfulness of canine life while providing insight into human quirks as observed by the observant dog. (This is an automatically generated summary.)
Release date is 2016-02-26
E-text prepared by David Edwards, ellinora, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Dogs -- Fiction; Dogs -- Humor